Improving Teachers' Numeracy Skills at Cisarua State Elementary School, West Java, Indonesia - Dikdik, Asep; Suryana, Asep; Rahyasih, Yayah; Oktaviani, Firyal Fatin; Triana, Cepi (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2025)
Teachers occupy a pivotal role in the education system, including the imperative of attaining numeracy competence, a benchmark defined by governmental standards. The objective of this study is twofold: firstly, to assess the current state of numeracy competence among teachers at Cisarua State Elementary School, and secondly, to formulate a model to enhance their competencies in this domain. The research methodology is quantitative, incorporating a case study design that amalgamates descriptive and exploratory research methodologies. The study's participants comprised 15 teachers evaluated through a questionnaire-based training needs survey. Data was collected through a survey technique, with a questionnaire as the primary instrument. The collected data underwent quantitative analysis using descriptive analysis techniques. The results indicated that teachers' numeracy competence falls below the ideal standard set by government policy, with an average score of 40.6 out of a possible 42. This discrepancy underscores the necessity for human resource development in numeracy competence. In light of these findings, this study proposes a training model based on the ICARE approach (Introduction, Connection, Application, Reflection, Extension) to enhance teacher numeracy competence. The implications of this study underscore the necessity of systematic and sustainable training interventions to enhance teachers' numeracy skills, which will contribute to enhancing the quality of numeracy learning for students at the primary school level.